FRI0486 LONG-TERM EFFICACY AND SAFETY OF CANAKINUMAB IN PATIENTS WITH AUTOINFLAMMATORY PERIODIC FEVER SYNDROMES – FIRST INTERIM ANALYSIS OF THE FMF/TRAPS/HIDS SUBGROUPS FROM THE RELIANCE REGISTRY. (2nd June 2020) - Henes, J.; Kuemmerle-Deschner, J. B.; Borte, M.; Foeldvari, I.; Horneff, G.; Kallinich, T.; Kortus-Goetze, B.; Weller-Heinemann, F.; Weber-Arden, J.; Blank, N.
Abstract : Background: Autoinflammatory periodic fever syndromes characterized by excessive interleukin(IL)-1b release and severe systemic and organ inflammation have been successfully treated with the anti-IL-1 inhibitor canakinumab (CAN). In clinical trial situations and real life, rapid remission of symptoms and normalization of laboratory parameters were observed in most patients. 1-3 Objectives: The present study explores long-term effectiveness and safety of CAN under routine clinical practice conditions in pediatric and adult patients with CAPS (cryopyrin-associated periodic syndromes), FMF (familial Mediterranean fever), TRAPS (tumor necrosis factor receptor-associated periodic syndrome) and HIDS/MKD (hyperimmunoglobulinemia D syndrome/mevalonate kinase deficiency). Methods: RELIANCE is a prospective, non-interventional, multi-center, observational study based in Germany with a 3-year follow-up period. Pediatric (age ≥2 years) and adult patients with clinically confirmed diagnoses of CAPS, FMF, TRAPS and HIDS/MKD that routinely receive CAN are enrolled in order to evaluate effectiveness and safety of CAN in clinical routine. Results: This first interim analysis of patient subgroups diagnosed with FMF, HIDS and TRAPS includes baseline data of 41 patients (10 TRAPS, 2 HIDS, 29 FMF), including preliminary 6-month data of a FMF-subset (N=16). Evaluation of disease activity and fatigue by patients' assessment, days absent from school/work, inflammatory markers and physician global assessment (PGA) was performed at baseline and will be further assessed at 6-monthly intervals within the 3-year observation period. Preliminary results of a first subset of 16 patients diagnosed with FMF are available and indicate stable remission and disease control upon long-term CAN treatment: within the first study interval, no major changes were observed regarding the analyzed parameters (table 1 ). Conclusion: Baseline characteristics of all subgroups and first interim data of FMF patients are available from the RELIANCE study, the longest running real-life CAN registry. Further interval data will be analyzed to assess efficacy and safety of long-term CAN-treatment in patients with autoinflammatory periodic fever syndromes. References: [1]Lachmann et al. N Engl J Med. 2009;360(23):2416-25 [2]Kuemmerle-Deschner et al. Rheumatology (Oxford). 2016;55(4):689-96 [3]De Benedetti et al. N Engl J Med. 2018;378(20):1908-1919 Disclosure of Interests: Jörg Henes Grant/research support from: Novartis, Roche-Chugai, Consultant of: Novartis, Roche, Celgene, Pfizer, Abbvie, Sanofi, Boehringer-Ingelheim, , J. B. Kuemmerle-Deschner Grant/research support from: Novartis, AbbVie, Sobi, Consultant of: Novartis, AbbVie, Sobi, Michael Borte Grant/research support from: Pfizer, Shire, Ivan Foeldvari Consultant of: Novartis, Gerd Horneff Grant/research support from: AbbVie, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bayer, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Tilmann Kallinich Grant/research support from: Novartis, Consultant of: Sobi, Roche, Novartis, Birgit Kortus-Goetze Consultant of: Novartis, Frank Weller-Heinemann: None declared, Julia Weber-Arden Employee of: I am employed by Novartis, Norbert Blank Grant/research support from: Novartis, Sobi, Consultant of: Novartis, Sobi, Lilly, Pfizer, Abbvie, BMS, MSD, Actelion, UCB, Boehringer-Ingelheim, Roche